Active thrust induced realignment of recent near-surface stresses in the Darjeeling-Sikkim Himalayas: Reasons and implications. (April 2021) - Das, Dip; Mallik, Jyotirmoy; Das, Shreeja; Deb, Tanwita; Das, Ayanangshu; Bandyopadhyay, Krishanu
Abstract: This paper presents a study where Fracture Induced Electromagnetic Radiation (FEMR) technique has been used to decipher the direction of recent near-surface stresses along the near surface segments of the major thrusts of the Darjeeling-Sikkim Himalaya, India. Slip Tendency analysis on the same thrust system was carried out where the sensitivity of the mutual angle between thrust strike and stress azimuth was tested. A major realignment of the regional surface stress was observed in specific areas of the Darjeeling-Sikkim Himalaya which perhaps indicate enhanced localized neotectonic activities. An attempt was made to test spatial correlation between landslide locations and areas with enhanced tectonic activity as predicted by the FEMR technique. We conclude that the newly practiced FEMR technique can be a fruitful shallow activity indicator of critically stressed fault systems which could cause shallow earthquakes and landslides. Highlights: FEMR technique is employed to prepare recent near surface stress azimuth map. Thrust parallel realignment of stresses are observed along some thrust segments. Such phenomenon is indicative of possible shallow neotectonic activities. Slip-tendency analysis suggests LHD is one of the most tectonically active area.